Wastewater-based microalgal biorefineries for the production of astaxanthin and co-products: Current status, challenges and future perspectives. (December 2021) - Nishshanka, Gannoru Kankanamalage Sanuji Hasara; Liyanaarachchi, Vinoj Chamilka; Premaratne, Malith; Nimarshana, P.H.V.; Ariyadasa, Thilini U.; Kornaros, Michael
Graphical abstract: Highlights: A critical review on wastewater-based cultivation of astaxanthin rich microalgae. Phycoremediation potential of H. pluvialis and C. zofingiensis in wastewater. Pretreatment of effluent for enhanced microalgae growth in wastewater. Cultivation of H. pluvialis and C. zofingiensis in wastewater for biorefining. Future perspectives in improving sustainability and concept of circular bioeconomy. Abstract: The freshwater microalgae Haematococcus pluvialis and Chlorella zofingiensis are attractive biorefinery feedstocks in view of their ability to simultaneously synthesize astaxanthin and other valuable metabolites. Nonetheless, there are concerns regarding the sustainability of such biorefineries due to the high freshwater footprint of microalgae cultivation. The integration of wastewater as an alternative growth media is a promising approach to reduce freshwater demand. Wastewater-based cultivation enables the recovery of essential nutrients required for microalgae growth and consequently results in phycoremediation of wastewater, thus promoting the concept of a circular economy and further enhancing the sustainability of the process. In this review, recent developments in wastewater-integrated cultivation of H. pluvialis and C. zofingiensis for astaxanthin production are discussed. Furthermore, prospective strategies for overcoming the inherent challenges of wastewater-based cultivation are reviewed. Moreover, the biorefinery potential of wastewater-grown H. pluvialis and C. zofingiensis is delineated and future perspectives of wastewater-based biorefineries are outlined.